Comparison of the acute effects of Tai chi versus high-intensity interval training on inhibitory control in individuals with substance use disorder - Yin, Yanqiang; Yang, Suyong; Xiao, Ke; Wang, Tianyuan; Wang, Jiabin; Schöllhorn, Wolfgang I.; Zhu, Dong; Pang, Xiaowu (Frontiers in Psychology, 2022)
Objective The purpose of this study is to investigate the effects of a single session of Tai chi (TC) exercise and high-intensity interval training (HIIT) on inhibitory control in individuals with substance use disorder (SUD). Methods A total 47 males with methamphetamine dependence were recruited from a compulsory drug rehabilitation center; participation in this study was voluntary. The participants were randomly assigned to the TC group or the HIIT group, and computer-based Go/No-go and Stroop tasks were used to assess inhibitory control in an indoor setting prior to and following exercise. Independent sample t-test was applied for baseline comparison of continuous variables, while analysis of variance was applied to test differences in the effect of each intervention before and after a single session of exercise. Results In Go/No-go test, the reaction time of the TC and HIIT groups in the post-test was shorter than that at the baseline, and the response accuracy of the post-test were higher than that of the baseline. In the Stroop task, the reaction time of two groups in the post-test was shorter than that at the baseline; while, greater improvement in response accuracy was observed in HIIT group in the post-test than that of the baseline. Conclusion Both TC and HIIT can promote inhibitory control in individuals with SUD. Compared with the TC group, the HIIT group showed greater improvements in response accuracy. These findings demonstrate the potential of TC and HIIT in improving cognition in SUD. Clinical trial registration [http://www.chictr.org.cn/], identifier [ChiCTR1900022158].